An Analysis of Management Accounting System Development from the Structuration Theory Viewpoint - Anthony Moung Yin CHAN (STIE Malangkucecwara, 2020)
Our study covered the development and evolution of the management accounting system of a subsidiary company in a group. Our study was a longitudinal one starting from the incorporation of the company. We divided this period into five stages according to the major events happened, namely the formation of the company, the invoicing crisis, the conflict with parent company, the conflict with fellow subsidiaries, and the influence of the chief executive. In our analysis we applied the three dimensions of structure in the theory of structuration (i.e., signification, legitimation and domination). The structuration theory explained the emergence of certain phenomena and events that were not explained by traditional accounting theories. Many events in our study validated the core ideas of the structuration theory which composes of the concepts of structure, system and duality of structure. The phenomena suggested that structure was both the medium and outcome of the conduct it recursively organized. Other features of the theory, such as the dialectic of control and system contradiction, were also applicable.